The First Record of Helobdella nuda (Hirudinida, Glossiphoniidae) in Lake Baikal - Kaygorodova, I.A.; Utevsky, S.Yu. (Вестник зоологии, 2012)
By far, the leech species Helobdella nuda (Moore, 1924) was known from China and the Amur River basin. It is found to occur in shallow waters of Lake Baikal.